PENGARUH MEDIA PEMBELAJARAN HAND PUPPET (BONEKA TANGAN) SEBAGAI MOTIVASI KETERAMPILAN BERCERITA SISWA SD NEGERI PALEMBANG - Nadia Oktaviani; Dian Nuzulia Armariena; Noviati (STKIP Subang, 2023)
This study aims to determine and describe the effect of hand puppet learning media on storytelling skills motivation of Palembang public elementary students. The research method used is the true experiment design method using the Postest Only, Non-Equivalent Control Group Design. In this study all of class V at SD Negeri 79 Palembang as a population. The sample collection technique uses purposive sampling. Data collection techniques using questionnaires and hypothesis testing in this study using the t-test (Independent Sample T-Test). The results of post-test results for the control class of 74.05 (medium category) and the average value of the pre-test results was 88.66 (high category). The results of the hypothesis analysis show that the sig two-tailed value is 0.019 with a decision making if the sig two-taliled value is smaller than (0.05) then Ho is rejected and Ha is accepted, which means there is a significant difference so that it can be concluded that hand puppet learning media has an effect on motivational storytelling skills fifth grade students at SD Negeri 79 Palembang. Keywords: hand puppet media, storytelling skills